Detection of Change Patterns in COVID-19 Deaths and the Implementation of Public Health Policies in Botswana - Lebotsamang Abidile; Morvyn Nyakudya (Masters Program in Public Health, 2025)
Background: At the earlier stages of COVID-19 disease, there were no pharmaceutical measures such as vaccines and medications available that could be used to either treat or reduce the spread of the virus. Countries worldwide reverted to implementing several non-pharmaceutical measures to end or at least reduce the spread of the COVID-19 pandemic. These included maintaining the physical distance of 1-2 meters in all gatherings, washing hands with soap and clean water, sanitizing hands, and wearing face masks especially when physical distancing cannot be certain. In this study, we aim to determine the change patterns or turning points in COVID-19 deaths, particularly those that occurred in Botswana.Subjects and Method: The study used a retrospective cohort study conducted in Botswana for a period ranging from the 14th May 2020 up to the 3rd March 2022. The population covered for this study comprised of all persons who were susceptible to COVID-19 in Botswana. The researcher used secondary data sourced from Botswana’s Ministry of Health and Wellness. Data for this study were statistically analysed using R software version 4.1.3 to apply the simulation methods.Results: High numbers of COVID-19 deaths in Botswana were recorded starting from week 59 to week 69 and the numbers declined from week 70 to week 75. Altogether, COVID-19 deaths in Botswana have been rising since 14th May 2020 until 3rd March 2022.Conclusion: It is important for the Government of Botswana through Ministry of Health and Well-ness to ensure that COVID-19 restrictions are slowly relaxed to avoid the recurrence of the disease. COVID-19 adherence protocols should be strictly enforced by the Ministry more especially during winter seasons as well as public holidays.